1984
DOI: 10.1037/0022-006x.52.6.1039
|View full text |Cite
|
Sign up to set email alerts
|

Change mechanisms in EMG biofeedback training: Cognitive changes underlying improvements in tension headache.

Abstract: Forty-three college students suffering from recurrent tension headache were randomly assigned to 1 of 4 elec-tromyographic (EMG) biofeedback training conditions. Although all subjects were led to believe they were learning to decrease frontal EMG activity, actual feedback was contingent on decreased EMG activity for half of the subjects and increased EMG activity for the other half. Within these 2 groups, subjects also viewed bogus video displays designed to convince them they were achieving large (high succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
1
7

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(141 citation statements)
references
References 38 publications
10
123
1
7
Order By: Relevance
“…Pain reduction may result in more adequate heart-related cognitions, or a third unknown variable may result in both reduced pain and more adequate cognitions. That pain reduction may be cognitively mediated has been shown in an experimental study of Holroyd et al [29]. These authors demonstrated that the effectiveness of non-cognitive procedures, such as biofeedback, may be mediated by cognitive changes independent of reductions in arousal.…”
Section: Discussionmentioning
confidence: 85%
“…Pain reduction may result in more adequate heart-related cognitions, or a third unknown variable may result in both reduced pain and more adequate cognitions. That pain reduction may be cognitively mediated has been shown in an experimental study of Holroyd et al [29]. These authors demonstrated that the effectiveness of non-cognitive procedures, such as biofeedback, may be mediated by cognitive changes independent of reductions in arousal.…”
Section: Discussionmentioning
confidence: 85%
“…Further, perceptions of control and self-efficacy have been linked to reduced sensitivity to pain (Averill, 1973;Bandura et al, 1987;Holroyd et al, 1984;Litt, 1988). For instance, perceptions of control and self-efficacy have been shown to affect sensitivity to pain during childbirth (Manning & Wright, 1983).…”
Section: * Corresponding Authormentioning
confidence: 99%
“…Ein interessantes Beispiel bezogen auf Kopfschmerzen stellt eine schon ältere Untersuchung zum EMG-Biofeedback von Holroyd et al (1984) dar. Dort wurden verschiedenen Behandlungsgruppen von Patienten mit Spannungskopfschmerzen teils wahrheitsgetreue und teils gefälschte EMG-Werte rückgemeldet.…”
Section: Kunden-und Patientenzufriedenheit Im Systemischen Forschungsunclassified